EDUCATIONAL EFFICIENCY OF THE TEACHERS OF STUDENTS WITH INTELLECTUAL DISABILITIES IN THE GOVERNORATE OF KERAK - Mohammad A. Yousef; Ahmad M. Bani Melhem (European Scientific Journal, ESJ, 2015)
The current study aims to know to what level teachers of students with intellectual disabilities have educational efficiency in the governorate of Kerak. To achieve the targets of this study, both researchers used the descriptive curricula, and the study tool was prepared to reveal how much teachers of students with intellectual disabilities have educational efficiency; whereas the tool consisted of (four) main dimensions that include (57) paragraph, both researchers developed it and extracted the necessary evidences of validity and stability, where they are distributed on (82) teachers of students with intellectual disabilities; where expected value, standard deviation and analysis of variance were used. Results of the study indicated that the level of educational efficiency of teachers for all dimensions of the study, was above average, and it was found that there are differences in the experience and qualification variables, but sex and sector did not have any statistical indicating effect.